Identification of Cordyceps javanica and its effectiveness in controlling bagworm, Pteroma pendula Joannis (Lepidoptera: Psychidae) - Syarif, Muhammad Nurul Yaqin; Asib, Norhayu; Ahmad, Siti Nurulhidayah; Ahamed Bakeri, Shamshilawani; Mohd Masri, Mohamed Mazmira; Omar, Dzolkhifli (Universiti Kebangsaan Malaysia, 2023)
The application of biological control agents as one of the control methods to suppress the infestation of bagworm in Malaysia has developed steadily with the inundation release of formulated entomopathogenic microbes to the outbreak area. In this study, we isolated and identified the entomopathogenic fungi (EPF) from the dead larvae of the bagworm, Pteroma pendula. Mycoses dead bodies of P. pendula were collected from two locations in Kemayan, Pahang, Malaysia. Morphological characterization of EPF was carried out by observing the macroscopic and microscopic growth on Potato Dextrose Agar (PDA) plates using a compound microscope. It was observed that white colonies on PDA changed into purple or pink shades after sporulation. The colony is slow-growing with floccose mycelium, which produces conidiophores with three to four phialides. The conidia were cylindrical to fusiform, smoothwalled and formed in chains on mononematous conidiophores. All the isolates were observed to be similar to Cordyceps fumosorosea features. Molecular identification using universal primer (ITS4 and ITS5) has identified that the isolates were Cordyceps javanica and Parahevansia koratensis. Bioassays of identified isolates were carried out against the second instar larvae of Pteroma pendula showed that C. javanica isolates BSB01 achieved LT50 - 6.76 days and recorded the shortest lethal time compared to the other isolates.